CAST POROUS MATERIALS AND TECHNOLOGIES OF THEIR PRODUCTION - A. A. Andrushevich; V. M. Kaptsevich; I. I. Gasper (Литьë и металлургия)
The characteristics of liquid metal, influencing on forming of cast porous material, produced by its infiltration through salt particles, are considered in the article. The technological processes of cast porous materials with metal base — aluminium-silicon alloy AK12, providing the obtaining of porosity 60-85 % and pore sizes 0,2-3,0 mm, are given.